2022
DOI: 10.22541/au.166942457.78014997/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The characterization of toll-like receptor repertoire in Pinna nobilis after mass mortality events suggests adaptive introgression.      

Abstract: The fan mussel Pinna nobilis is currently on the brink of extinction due to a multifactorial disease mainly caused to the highly pathogenic parasite Haplosporidium pinnae, meaning that the selection pressure outweighs the adaptive potential of the species. Hopefully, rare specimens have been observed somehow resistant to the parasite, stretching the need to identify the traits underlying this better fitness. Among the candidate to explore at first intention are fast evolving immune genes, of which toll-like re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Moreover, considering the findings of Coupé et al [47] that some P. nobilis individuals that introgressed with P. rudis were resistant to infection by Haplosporidium pinnae, the expansion of P. rudis in the Mediterranean could lead to an increased frequency of hybridisation and introgression with P. nobilis. This, in turn, could confer resistance to H. pinnae, a primary etiological agent of mass mortality events, thereby potentially promoting the recovery and survival of the fan mussel.…”
Section: Phylogeny Of Pinna Nobilismentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, considering the findings of Coupé et al [47] that some P. nobilis individuals that introgressed with P. rudis were resistant to infection by Haplosporidium pinnae, the expansion of P. rudis in the Mediterranean could lead to an increased frequency of hybridisation and introgression with P. nobilis. This, in turn, could confer resistance to H. pinnae, a primary etiological agent of mass mortality events, thereby potentially promoting the recovery and survival of the fan mussel.…”
Section: Phylogeny Of Pinna Nobilismentioning
confidence: 97%
“…The initial investigations into the causes of the MME of P. nobilis primarily concentrated on the search for protozoa [29,30,32,33,[40][41][42], and histological analysis on the first affected individuals of P. nobilis revealed the presence of a haplosporidian-like parasite (Haplosporidium pinnae) within the digestive gland [29,30,40], initially believed to be host-specific for fan mussels. Subsequent studies identified several bacterial species as potential pathogens contributing to the MME of P. nobilis [13,[35][36][37]39,[43][44][45][46], indicating that the disease is a multifactorial pathology [13,47,48]. Scarpa et al [13] also reported the finding of H. pinnae in other bivalve species collected before 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The search for survivors is requiring a large sampling effort, partly supported by citizen science. In this context, an unusual number of P. rudis individuals, apparently unaffected by pathogens [21], has been recorded in various, newly discovered locations across the Mediterranean, indicating that the species is expanding its range northward and eastward [22][23][24][25].…”
mentioning
confidence: 99%